Are malaysian consumers willing to pay for hybrid cars’ attributes? - Hasan Basri, Bakti; Mohd Mustafa, Muzafarshah; Bakar, Normizan (Universiti Kebangsaan Malaysia, 2019)
The Malaysian government has recently introduced a new National Automotive Policy in 2014. The policy aims to make Malaysia an Energy Efficient Vehicle (EEV) and component production hub for the ASEAN region. Since consumers’ preference of Hybrid Cars (HCs)/EEVs is strongly influenced by the attributes of those cars, thus this study wishes to investigate whether respondents’ preference for HCs is due to environmental or economic attributes. The study uses Choice Experiment technique where respondents’ preference are measured in terms of their Willingness to Pay for such attributes. Two formats of factors are applied, bundle of attributes and individual attributes. The objective of applying these two factors is to investigate whether bias in Independent Valuation and Summation (IVS) happens or not. The results on bundle show that the respondents prefer environmental attributes more than economic attributes when buying HCs. In terms of IVS, we found that bias in IVS does not occur. Three policy implications can be drawn. First, the Malaysian government needs to take necessary measures if they are keen to encourage the public to buy HCs. Second, more understanding and awareness campaigns on HCs need to be done by the government. Third, the noise levels of the engine is an important attribute that needs to be considered in developing the EEV industry in Malaysia.